The Prevalence of Nomophobia among University Students and Nomophobia’s Relationship with Social Phobia: The Case of Bingöl University - Apak, Emrah; Yaman, Ömer Miraç (Addicta: The Turkish Journal on Addictions, 2019)
The aim of this study is to determine the relationship between nomophobia and social phobia and the prevalence of nomophobia (NO-MObile-PHOne-PhoBIA) among university students. Within the scope of the research, 307 students studying at Bingöl University’s Department of Social Work were reached. In order to collect data, a demographic information form with questions about age, grade, and gender was applied alongside the Nomophobia Scale and the Liebowitz Social Anxiety Scale. According to the results of the study, 41% of the participants are nomophobic. As a result of the study, a low positive correlation has been found between nomophobia and social phobia. These results show nomophobia to have become a rapidly spreading problem among university students and preventive studies to be required on the factors affecting nomophobia and social phobia. To